Marine Square, Trinidad - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
The postcard shows the northern side of Marine Square which was renamed Independence Square in 1962. A sign hanging on one of the buildings here reads: Stationery; Fancy goods; Photo goods; Job printing; Muir Marshall and Co. In the background a tram car can be seen.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Stores, Retail--Trinidad and Tobago; Architecture--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Marine Square (Port of Spain); Independence Square (Port of Spain)